Interaction between Literature and Law - de Trazegnies Granda, Fernando (2016)
The seventeenth century represents formankind the creation of great literary works that narrate the events that occurred in the reality of that time flawlessly. This article wants to analyze the implications and reviews of some literary texts by renowned authors of that time like Miguel de Cervantes and William Shakespeare with modern legal institutions. Also, to think about how literature enriches the science of law.